Economic perspectives on blanket and selective dry cow therapy - Heikkilä, Anna-Maija; Niemi, Riitta E.; Rajala-Schultz, Päivi J. (Agricultural and Food Science, 2022)
Dry cow therapy (DCT) is an efficient measure to control intramammary infections (IMI) in dairy herds. In a blanket- DCT practice (BDCT), all cows receive antibiotics at dry-off. In a selective-DCT practice (SDCT), treatments are targeted only at infected cows. Our objective was to compare the economy of SDCT and BDCT under Finnish production conditions. Economic analysis is needed to show numerically whether the farms currently applying BDCT can switch to SDCT without the dairy farmer’s economic losses. We applied a partial budgeting approach and built a stochastic calculation model to show the margin for costs that are equal in both DCT policies. Data for modeling were generated by running 100,000 Monte Carlo simulations. The parameters for the model were extracted from the literature and from official statistics. SDCT is a competitive management practice, especially with herds succeeding in keeping their IMI risk low. Therefore, the focus in farm-level decision-making should be on the herd’s udder health status. In those herds with high IMI prevalence, the problem must be tackled primarily by means other than BDCT, which does not support the goal of reducing the use of antibiotics and which, when used routinely, is also contrary to existing EU legislation.